أثر مجالس الأنس والسمر في العبث بالأخبار الجاهلية في روايات كتاب الأغاني إنموذجا - حمد محراث, حمد محراث; عادل محسن, عادل محسن (Journal of College of Education, 2020)
This research showed that some of the novels of love stories were given to the readers and enjoyment of them, and its fabric was from the queen and imagination of the narrators who were famous for the story, who used to hear their literary tales in funny ways that touch the popular taste and the general public, and this led to the creation of a class or class known for trading novels and stories. Its purpose is to bring in money .. As the increase in demand led to the abundance of news and narratives woven from their imaginations in abundance and competition in those markets, without keenness in searching and exploring the correct sources that they conveyed, and they deluded the readers with their supposed putative prophets, and this category increased and increased its danger in The historical legacy of literature in general, and if we seek in this research to lay our hands on a section of it in the pre-Islamic era.